Increased implantation and pregnancy rates obtained by placing the tip of the transfer catheter in the central area of the endometrial cavity - Oliveira, João Batista Alcantara; Martins, A. M V C [UNESP]; Baruffi, R. L R; Mauri, A. L.; Petersen, C. G.; Felipe, V.; Contart, P.; Pontes, Anaglória [UNESP]; Franco, J. G. (Elsevier, 2004)
The influence of endometrial cavity length (ECL) on implantation and pregnancy rates after 400 embryo transfers was studied prospectively in a population with the indication of IVF/intracytoplasmic sperm injection (ICSI). The tip of the transfer catheter was placed above or below the half point of the ECL in a randomized manner. Two analyses were performed: (i) absolute position (AP); embryo transfers were divided into three groups according to the distance between the end of the fundal endometrial surface and the catheter tip (DTC - distance tip catheter): AP 1 (n = 212), 10-15 mm; AP 2 (n = 158), 16-20 mm; and AP 3 (n = 30), ≥21 mm. (ii) relative position (RP) - embryo transfers were divided into four groups according to their RP [RP = (DTC/ECL) × 100]: RP 1 (n = 23), ≤40%; RP 2 (n = 177), 41-50%; RP 3 (n = 117), 51-60%; and RP 4 (n = 83), ≥61%. Analysis based on relative distance revealed significantly higher implantation and pregnancy rates (P < 0.05) in more central areas of the ECL. However, analysis based on absolute position did not reveal any difference. In conclusion, the present results demonstrated that implantation and pregnancy rates are influenced by the site of embryo transfer, with better results being obtained when the catheter tip is positioned close to the middle area of the endometrial cavity. In this respect, previous analysis of the ECL is the fundamental step in establishing the ideal site for embryo transfers.
Keywords: Embryo transfer; Emdometrial cavity length; Implantation rates; IVF/ICSI; Pregnancy rates; nafarelin acetate; recombinant follitropin; adult; catheterization; clinical trial; controlled clinical trial; controlled study; embryo; embryo transfer; endometrium; female; fertilization in vitro; human; intracytoplasmic sperm injection; nidation; organ size; ovulation induction; pregnancy rate; prospective study; randomized controlled trial; treatment indication; Adult; Catheterization; Embryo Transfer; Endometrium; Female; Fertilization in Vitro; Humans; Pregnancy; Prospective Studies; Sperm Injections, Intracytoplasmic